Personality Functioning in Inpatients With Eating Disorders: Association With Symptom Severity and Treatment Outcome - Heinzmann, Sophia; Etzler, Sonja; Hartmann, Armin; Klein, Eva M.; Herpertz, Stephan; Pape, Magdalena; Heinzmann, Stanislav; Doering, Stephan; Hofmann, Tobias; Rose, Matthias; Imbierowicz, Katrin; Geiser, Franziska; et al. (European Eating Disorders Review, 2025)
Objective: Impairment in personality functioning (PF) has been linked to a number of mental disorders, including eating disorders (EDs). However, the precise relationship between PF and symptom severity, as well as the potential impact on outcome, remains unclear. The study aimed to analyse the association of PF and its change with severity of ED symptomatology as well as outcome of hospital treatment. Method: The sample consisted of 397 patients with EDs, treated in 19 university hospitals for Psychosomatic Medicine and Psychotherapy in Germany between 1/2019 and 12/2020. PF was measured with the Structure Questionnaire of the Operationalised Psychodynamic Diagnosis (OPD-SQ, short version), eating psychopathology with the ED examination questionnaire (EDE-Q). Outcome was defined as a change in the EDE-Q total score. We used Latent Change Score Modelling to analyse changes in ED pathology during treatment and a 1-year follow-up period. Results: A higher level of impairment in PF at admission correlated with more eating psychopathology and a less favourable outcome. Additionally, greater improvement in PF correlated with greater improvements in ED symptomatology at discharge. Conclusion: Impairment in PF needs to be part of diagnostic assessments and should be considered an important treatment target for psychotherapeutic interventions. Trial Registration: The MEPP study was registered in the German Clinical Trials Register (DRKS, www.drks.de; ID: DRKS00016412).
CRIS-Team Scopus Importer:2025-03-14
Keywords: eating disorder; inpatient; latent change score model; personality functioning; psychotherapy